Bleeding manifestations of congenital and drug-induced defects of the platelet P2Y12 receptor for adenosine diphosphate - Cattaneo, Marco (Thrombosis and Haemostasis, 2011)
P2Y12, one of the two platelet receptors for adenosine diphosphate (ADP), plays a central role in platelet function. Defects of P2Y12 should be suspected when ADP, even at high concentrations (≥10 μM), is unable to induce full, irreversible platelet aggregation. Patients with congenital P2Y12 defects display a mild-to-moderate bleeding diathesis of variable severity, characterised by mucocutaneous bleeding and excessive post-surgical and post-traumatic blood loss. Drugs that inhibit P2Y12 are potent antithrombotic drugs, attesting the central role played by P2Y12 in platelet thrombus formation. Clopidogrel, the most widely used drug that inhibits P2Y12, is effective both in monotherapy and in combination with acetylsalicylic acid (ASA). Its most important drawback is the inability to inhibit adequately P2Y12-dependent platelet function in about 1/3 of patients, at the recommended therapeutic doses. The incidence of bleeding events is similar in ASA-treated and clopidogrel-treated patients; however, the combination of ASA and clopidogrel causes more bleeding than each drug in monotherapy. Compared to clopidogrel, new drugs inhibiting P2Y12, such as prasugrel and ticagrelor, decrease the risk of cardiovascular events and increase the risk of bleeding complications, because they adequately inhibit P2Y12-dependent platelet function in the vast majority of treated patients.
Keywords: ADP receptors; antiplatelet drugs; coronary syndrome; inherited / acquired platelet disorders; platelet pharmacology